PENGARUH EKSTRAK ETANOL DAUN KELAPA SAWIT (Elaeis guineensis Jack.) TERHADAP PERTUMBUHAN Staphylococcus aureus dan Escherichia coli BERDASARKAN METODE KLT-BIOAUTOGRAFI - Istianah Purnamasari; Muhammad Taufiq Duppa; Syafruddin Syafruddin; Sitti Nurjanna; Anshari Masri; Hernawati Basir; Ermawati Ermawati (Jurnal Kesehatan Yamasi Makassar, 2026)
This study aims to determine the antibacterial activity of ethanol extract of oil palm leaves (Elaeis guineensis Jack.) against the growth of Staphylococcus aureus and Escherichia coli and to determine the compounds from ethanol extract of oil palm leaves (Elaeis guineensis Jack.) that can provide antibacterial based on TLC-Bioautography analysis. This study tested the antibacterial activity of ethanol extract of oil palm leaves (Elaeis guineensis Jack.). Ethanol extract of oil palm leaves was obtained through the maceration method. Then the activity test was carried out by TLC-Bioautography against Staphylococcus aureus and Escherichia coli bacteria. The results of the separation of compounds by Thin Layer Chromatography (TLC) using n-hexane: ethyl acetate (7: 3) eluent. The results of the TLC-Bioautography test showed that spots at Rf values ​​0.92; Rf 0.85; Rf 0.74; Rf 0.7; Rf 0.63 and Rf 0.52 can provide inhibitory activity against Staphylococcus aureus and at Rf values ​​​​of 0.92; Rf 0.85 can provide inhibitory activity against Escherichia coli. The results of the identification of chemical components gave positive results in the appearance of flavonoid spots at Rf values ​​​​of 0.92; Rf 0.85 and alkaloids at Rf values ​​​​of 0.92; Rf 0.74.